Penggunaan Media Roda Putar sebagai Alat Pemilihan Peran pada Sentra Peran di Paud Islam Hidayatullah Semarangx - Ramadhanty, Dahniar; Tasuah, Neneng (Universitas Negeri Padang, 2024)
This study was conducted with the aim of selecting roles using the rotating wheel media game. There are children who do not want to play roles in the role center and tend to choose to play alone. The rotary wheel is a game media that can be used to support learning activities in the classroom. The rotary wheel game is used before the center play activities begin. This research method uses qualitative research with class action techniques. Researchers conducted learning using the rotary wheel media as a role selection tool at the role center of Play Group 1. The media is made manually with a variety of diverse tools and materials. The use of the rotary wheel media is by rotating the rotary wheel, then after the wheel stops the students will get a role from the media to play in the role center. Rotary wheel media has various advantages and disadvantages of its use. Based on the conclusions, there are positive changes from students after the use of the rotary wheel media takes place. After the existence of the rotary wheel media game as a role selection tool, students are very enthusiastic and willing to play roles in the role center.